KEANEKARAGAMAN MARGA JAMUR PATOGEN PADA BIJI KACANG TANAH (Arachis hypogaea L.) DI PASAR TRADISIONAL KECAMATAN KEDATON, BANDAR LAMPUNG - Annida Amalia Fatin; Yulianty Yulianty; Lili Chrisnawati; Sri Wahyuningsih (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2026)
This study aims to identify the diversity and dominant genera of pathogenic fungi contaminating peanut (Arachis hypogaea L.) seeds sold in traditional markets in Kedaton District, Bandar Lampung. Peanut samples were collected from seven traditional markets using purposive sampling and analyzed through macroscopic and microscopic observations. Fungal isolation was performed using Potato Dextrose Agar (PDA), followed by identification using slide culture techniques and standard fungal identification keys. The findings revealed three fungal genera, namely Aspergillus sp., Rhizopus sp., and Penicillium sp. Aspergillus sp. was found to be the most dominant, appearing in 16 out of 21 samples. The dominance of Aspergillus sp. is associated with its strong ability to grow in warm, humid, and open storage environments typical of traditional markets. The presence of these fungi is of concern, as some species are known to produce harmful mycotoxins that may threaten food safety. The study concludes that pathogenic fungal contamination in peanuts is common in traditional markets, highlighting the need for improved postharvest handling and storage practices.